ANALISIS KINERJA KEUANGAN PEMERINTAH KOTA BANDUNG PERIODE 2020–2024 BERDASARKAN RASIO KEUANGAN DALAM PERSPEKTIF DESENTRALISASI FISKAL - Levina Khulaidah; Syifa Rhamadani; Fadjar Tri Sakti (ANALISA : JURNAL MANAJEMEN DAN AKUNTANSI, 2025)
This study aims to analyze the financial performance of the Bandung City Government during the 2020–2024 period from a fiscal decentralization perspective. The research employs a descriptive quantitative method using secondary data obtained from the Directorate General of Fiscal Balance (DJPK) of the Ministry of Finance. The analysis applies seven regional financial ratios, namely the degree of fiscal decentralization, regional financial independence, fiscal dependency, effectiveness of Local Own-Source Revenue (PAD), expenditure efficiency, expenditure harmony (operational and capital expenditures), and growth ratio. The results indicate that the financial performance of the Bandung City Government has shown improvement, as reflected in the increasing levels of fiscal decentralization and financial independence. However, fiscal dependency remains relatively high, the effectiveness of PAD has not been optimal, and expenditure efficiency is still classified as less efficient. The expenditure structure is dominated by operational spending, while capital expenditure allocation remains relatively low. In addition, regional revenue growth during the study period is considered low and unstable. Therefore, optimizing PAD, improving expenditure efficiency, and restructuring the budget composition are necessary to support sustainable fiscal decentralization. Keywords: Fiscal decentralization, Regional financial performance, Bandung city, Local owns source revenue, Regional financial rations